Crystal structure prediction of ReN at high pressure: a new incompressible phase. (3rd June 2019) - Wang, H. Y.; Yan, P.; Xu, L.; Zhou, D. W.
ABSTRACT: Based on the swarm-intelligence-based CALYPSO method the NbO, R 3 m and NiAs phases for ReN are predicted. The R 3 m phase of ReN at high pressure is firstly found. The structural, mechanical and electronic properties of ReN with the three phases are studied systematically. Moreover, it is also firstly found that pressure stimulated ReN to undergo twice phase transitions, from NbO to R 3 m phase at 43.3 GPa and from R 3 m to NiAs phase at 53.6 GPa. The three phases of ReN are verified to be mechanically stable and a promising low-compressible material at ambient conditions. According to the electron density of states and electron localization functions we have found that their structural stability and high hardness is on account of the strong covalent bonding of Re-N and N-N.